Origin, prospective identification, and function of circulating endothelial colony-forming cells in mice and humans - Yang Lin; Kimihiko Banno; Chang-Hyun Gil; Jered Myslinski; Takashi Hato; William C. Shelley; Hongyu Gao; Xiaoling Xuei; Yunlong Liu; David P. Basile; Momoko Yoshimoto; Nutan Prasain; et al. (JCI Insight, 2023)
Most circulating endothelial cells are apoptotic, but rare circulating endothelial colony-forming cells (C-ECFCs), also known as blood outgrowth endothelial cells, with proliferative and vasculogenic activity can be cultured; however, the origin and naive function of these C-ECFCs remains obscure. Herein, detailed lineage tracing revealed murine C-ECFCs emerged in the early postnatal period, displayed high vasculogenic potential with enriched frequency of clonal proliferative cells compared with tissue-resident ECFCs, and were not committed to or derived from the BM hematopoietic system but from tissue-resident ECFCs. In humans, C-ECFCs were present in the CD34bright cord blood mononuclear subset, possessed proliferative potential and in vivo vasculogenic function in a naive or cultured state, and displayed a single cell transcriptome sharing some umbilical venous endothelial cell features, such as a higher protein C receptor and extracellular matrix gene expression. This study provides an advance for the field by identifying the origin, naive function, and antigens to prospectively isolate C-ECFCs for translational studies.